DEMOCRACY, RULE OF LAW AND HUMAN RIGHTS IN THE CONTEXT OF EUROPEAN INTERGATION OF UKRAINE - Колодій, А. М. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article examines the concept of democracy through the coverage of its features, the rule of law and the source of protection of human rights and citizen, and also proposes measures to ensure the process of European integration of Ukraine.